Suprachoroidal triamcinolone acetonide versus rescue therapies for the treatment of uveitic macular oedema: A post hoc analysis of PEACHTREE. (27th December 2021) - Singer, Michael A.; Merrill, Pauline; Yeh, Steven; Hall, Colette; Kapik, Barry; Ciulla, Thomas A.
Abstract: Background: This post hoc analysis compared the efficacy and safety of suprachoroidally administered triamcinolone acetonide (CLS‐TA) to other commonly available treatments for non‐infectious uveitis. Methods: Results from the PEACHTREE study were compared between subjects randomised to CLS‐TA not requiring rescue therapy and those subjects randomised to control, who subsequently required rescue therapy. Endpoints included best corrected visual acuity (BCVA), central subfield thickness (CST), treatment emergent adverse events and intraocular pressure (IOP) related safety findings. Results: In this analysis, there were 83 unrescued CLS‐TA subjects and 46 rescued control subjects. At Week 24, 51.9% of the unrescued CLS‐TA subjects gained ≥15 letters in BCVA, compared to 37.0% of the rescued control subjects ( p  = 0.115). Unrescued CLS‐TA subjects showed a mean gain of 15.7 versus 10.9 letters in rescued control subjects ( p  = 0.080). A significantly greater mean reduction in CST was observed for unrescued CLS‐TA subjects versus rescued control subjects (174.0 and 148.5 μm; p  = 0.040). Of unrescued CLS‐TA subjects, 4.9% experienced IOP elevations ≥30 mm Hg at any visit versus 10.9% of rescued control subjects. Further, use of IOP‐lowering medications appeared lower in unrescued CLS‐TA subjects versus rescued control subjects (7.2% vs. 13.0%). There were no IOP‐lowering surgical interventions in either group. Conclusion: CLS‐TA subjects experienced significantly greater reduction in CST and tended towards greater improvement in BCVA, compared with rescued control subjects. Suprachoroidally administered CLS‐TA showed a lower incidence of IOP‐related safety findings.